THE CHANGING FACE OF URGENT NEUROLOGY OUTPATIENT REFERRALS. Issue 11 (9th October 2013) - Fiddes, Barnaby; Adam, Robert; Donaghy, Alastair; Whyte, Adam; Allen, Chris
Abstract : Introduction: A recent report published jointly by the RCP and ABN found that neurological presentations accounted for a significant proportion of GP and emergency room time, but access to acute neurological services was lacking. A study of urgent neurology outpatient referrals from primary health care physicians in Cambridge was first carried out in 1995 with the purpose of identifying which patients genuinely required urgent assessment, and the type of pathology seen. We thought it would be interesting to repeat this study a decade later to see whether there has been any change in the nature of neurological presentation, especially given recent changes in (for example) government health targets, waiting list initiatives, availability of imaging, and changes to local neurological services. Method: Patients are referred to the neurology registrar on call, and they are booked in to the next available (weekday) emergency clinic slot. 458 patients were seen during 2008 and 2009, of which we had information for 415. Data was collected retrospectively from the original emergency clinic letter, follow up clinic letters, and investigation results. Results: Seventy–five per cent of referrals were from general practitioners, most of which were within a 30 mile radius of Cambridge. Demand for an emergency clinic service has remained just as high, but there has been a clear change in presenting symptom and pathology seen, with more headaches (48%, compared to 27% in 1995), sensory limb disturbance (35% vs. 10%), and dizziness (19% vs. 5%). Conversely, fewer patients were seen with loss of consciousness (6% vs. 13%). 19% of patients were previously known to neurology, and of these 13% were patients with MS, compared to 42% in 1995. There were positive neurological examination findings in 60% of patients, the majority of which were focal cerebral. Only 7% of patients were admitted (compared to 19% in 1995), 52% were followed up in a neurology clinic, 12% were referred to a different specialty, and 32% were discharged. Following investigation, a definite 'neurological' diagnosis was made in 75% of patients, although this included headaches of all aetiologies (43% if excluded). Discussion: There is still a clear need for an acute neurology clinic service given the high percentage of neurological diagnoses made. However, there is a clear change in pattern of presentation and diagnosis over the period 1995–2008. Far fewer patients were seen with loss of consciousness and MS relapses, a fact likely to be explained by the growth of other 'rapid access' services, such as a daily first seizure clinic and a nurse led community MS team. Just as many patients are being seen, and this may suggest that demand has grown to fill supply; referrals with more benign pathology have increased, in particular those for headache and dizziness. Emergency admission from the clinic is less common, and this may be due to improved availability of outpatient MRI and lumbar punctures in our programmed investigation unit, and also more structured outpatient pathways such as that for CNS tumours.